2007
DOI: 10.3113/fai.2007.1064
|View full text |Cite
|
Sign up to set email alerts
|

Three-year Followup Study of Topical Glyceryl Trinitrate Treatment of Chronic Noninsertional Achilles Tendinopathy

Abstract: Topical glyceryl trinitrate treatment has demonstrated efficacy in treating chronic noninsertional Achilles tendinopathy, and the treatment benefits continue at 3 years. Significant differences in asymptomatic patient outcomes for the glyceryl trinitrate group continue at 3 years, and this is confirmed by the effect size estimate. This suggests that the mechanism of action of topical glyceryl trinitrate on chronic tendinopathies is more than an analgesic effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(58 citation statements)
references
References 23 publications
0
57
0
1
Order By: Relevance
“…It is very important to keep separate the two concepts of perfusion and neovascularization: on the one side, thanks to the perfusion, that represents the blood flow per unit of time, nutrients and oxygen are transported in the tissue and toxic molecules removed; on the other side it has already been discussed the pathogenetic role of neovascularization, which, even if it could be regarded as attempt at healing, leads at the end to tendon weakening. These findings justify the current interests to investigate the potentially beneficial role of drugs containing L-arginina alphachetoglutarate (AAKG), the specific precursor of NO, in Achilles tendinopathy [74,121] . Concluding this analisys of the effects of overuse on tendons, it must be remembered that recent studies found tendon stem cells (TSCs) in human and animal tendon tissue [122,123] .…”
Section: The Role Of Nitric Oxide (No) and Tendon Stem Cells (Tscs)mentioning
confidence: 81%
“…It is very important to keep separate the two concepts of perfusion and neovascularization: on the one side, thanks to the perfusion, that represents the blood flow per unit of time, nutrients and oxygen are transported in the tissue and toxic molecules removed; on the other side it has already been discussed the pathogenetic role of neovascularization, which, even if it could be regarded as attempt at healing, leads at the end to tendon weakening. These findings justify the current interests to investigate the potentially beneficial role of drugs containing L-arginina alphachetoglutarate (AAKG), the specific precursor of NO, in Achilles tendinopathy [74,121] . Concluding this analisys of the effects of overuse on tendons, it must be remembered that recent studies found tendon stem cells (TSCs) in human and animal tendon tissue [122,123] .…”
Section: The Role Of Nitric Oxide (No) and Tendon Stem Cells (Tscs)mentioning
confidence: 81%
“…17 Paoloni et al demonstrated the efficiency of one 1.25 mg patch/day over a 6-month period in a double-blind study of supraspinatus tendinopathy 14 and Achilles tendinitis. 18 Moreover, the latter study reports that a lower level of awareness of pain was maintained after a 3-year treatment period, which indicates that the NT function mechanism is not merely analgesic. 18 Nonetheless, one recently published work 12 has aroused controversy because its results oppose the assumed effect of NT on collagen regeneration in damaged tendons.…”
Section: Discussionmentioning
confidence: 89%
“…18 Moreover, the latter study reports that a lower level of awareness of pain was maintained after a 3-year treatment period, which indicates that the NT function mechanism is not merely analgesic. 18 Nonetheless, one recently published work 12 has aroused controversy because its results oppose the assumed effect of NT on collagen regeneration in damaged tendons. This recent study indicates that NT offers no additional benefit to the standard conservative treatment.…”
Section: Discussionmentioning
confidence: 89%
“…50,51 Studies of the long-term efficacy of nitroglycerin patches, however, have generally shown marginal to no improvement in pain and function. 52 Side effects of nitroglycerin patches have also been reported, including headache, rash, facial flushing, and sweating. 49 These potential side effects along with the contradictory short-term results and the lack of long-term efficacy have limited the T A B L E 1 Summary of non-operative and operative therapeutic interventions for the management of tendinopathy…”
Section: Nitric Oxidementioning
confidence: 99%